Use of humic acid in the treatment of salt solutions using the germination percentage as a guide to treatment laboratory (Journal of the College of Basic Education, 2023)
Experiment was conducted, to study the effect of addimg different volume of humic to different concentrations of sodium chloride(NaCl) on plant seed germination. cucumber seeds ( high sensitivity to salinity ) were selected as an index for percentage of germination which was calculated after a week of nursing Results indicated that Lack of seed germination of cucumber plant in salt solutions with concentrations of the following ((5000,7000,10000,14000 ppm, but the Irrigation with salt solutions (mentioned above)+ humic acid up to 3400 micro gram) led to significant increase in germination percentage in all salt concentrations so it do well for control salinity effect.